Generation of viable calves derived from developmentally mature blastocysts produced by on-gel culture - Shun SAITO; Hiroki AKIZAWA; Eri FURUKAWA; Yojiro YANAGAWA; Hanako BAI; Masashi TAKAHASHI; Manabu KAWAHARA (The Society for Reproduction and Development, 2022)
Conventional culture systems for bovine embryos are unable to support sustained embryonic development until the developmentally mature blastocyst stage. Although we have previously developed an on-gel culture system that enables bovine blastocysts to complete cell segregation events at day (D) 10 following in vitro culture, the development of D10 blastocysts to term has yet to be achieved. In this study, we attained full-term development of D10 mature blastocysts produced using an on-gel culture system. Two calves derived from on-gel-cultured embryos were vaginally born, showing normal birth and placental weights and no obvious morphological abnormalities. Moreover, we detected no abnormalities in blood metabolic profile analyses. Our findings indicate that on-gel culturing can be used to facilitate the development of developmentally mature blastocysts to term, and produce healthy viable calves. This culture system could make a valuable contribution to cattle production and would enable a range of analyses for characterizing bovine-specific pre-implantation development.